2015
DOI: 10.1209/0295-5075/112/36005
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between normal-fluid and superfluid vortex rings in helium-4

Abstract: -By employing both vortex-dynamical and self-consistent Navier-Stokes methods of analysis, an investigation of interactions between normal-fluid and superfluid vortex rings in helium-4 is performed. It is shown that, under the influence of normal-fluid vortices, superfluid vortices grow in size in order to match the size of the latter. In turbulence, this mechanism hints to a tendency towards scale-to-scale energy equipartition in the spectral regimes corresponding to the inertial-range in the normal-fluid. Ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
(32 reference statements)
5
9
0
Order By: Relevance
“…shows normal-fluid vorticity isosurfaces (|ω| = 37000 s −1 ) as they coevolve with a dilute tangle of superfluid vortices. In agreement with previous investigations[18], the solution indicates that although the generation sites of superfluid vorticity are somewhat Normal-fluid Hopf-link interacting with superfluid vortices of similar diameters. Left:Flow energy E = (1/2V) dV V • Vversus time.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…shows normal-fluid vorticity isosurfaces (|ω| = 37000 s −1 ) as they coevolve with a dilute tangle of superfluid vortices. In agreement with previous investigations[18], the solution indicates that although the generation sites of superfluid vorticity are somewhat Normal-fluid Hopf-link interacting with superfluid vortices of similar diameters. Left:Flow energy E = (1/2V) dV V • Vversus time.…”
supporting
confidence: 91%
“…The observed instabilities appear similar to the Ostermeier-Glaberson instability [36], that Another important result (see also [18]) is that the superfluid rings do not grow at sizes quantities is expected to be small. Indeed, only mild variations of the pure normal-fluid solution are observed.…”
Section: Interactions Between Rings Of Similar Sizesupporting
confidence: 53%
See 2 more Smart Citations
“…For example, [8] indicated that a system of viscous, reconnecting vortex tubes reproduces the Kolmogorov k −5/3 scaling of inertial range turbulence, and [9] showed that systems of vortex elements give rise to Levy rather than Gaussian distributions for turbulent flow velocity. Similar connections between vortices and spectra [10][11][12], as well as, vortices and velocity distributions [13,14] were also obtained in quantum fluids. In FTST, [12] showed that interactions between one normal-fluid and many superfluid vortex rings generate a tendency towards energy-level matching in the wavenumber intervals of the velocity spectra which correspond to the normal-fluid ring diameter scale.…”
supporting
confidence: 58%